2005
DOI: 10.1128/mcb.25.24.11030-11034.2005
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of the Role of Ubiquitin-Like Modifier ISG15 in the Phenotype of UBP43-Deficient Mice

Abstract: UBP43/USP18 was described as a specific protease that removes conjugated ubiquitin-like modifier ISG15 from target proteins. The severe phenotype of UBP43 ؊/؊ mice characterized by premature death, brain cell injury, and deregulated STAT1 signaling was ascribed to an enhanced conjugation of ISG15. In contrast, no phenotypic changes were detected in ISG15 ؊/؊ mice. To verify the role of ISG15 in the phenotype of UBP43؊/؊ mice, we employed mice deficient for both ISG15 and UBP43. Here, we show that the phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 21 publications
5
83
1
Order By: Relevance
“…Our data showed that a variety of CXC (CXCL10, CXCL11) and CC chemokines (CCL2, 3, 4 and 5) as well as CC chemokine receptor (CCRL2) are induced by IFN-β in Ubp43 −/− BMMs (Fig. 4 and supplemental data Although there are arguments about the effect of Ubp43 deficiency on the IFN signaling pathway and the expression of IFN stimulated genes [14], our present study using Microarray analysis reveals that Ubp43 deficiency in BMMs generally enhanced the expression of genes that are induced by IFN in wild-type cells. The IFN hypersensitivity of Ubp43 −/− cells and subsequent higher induction of immune response related genes in Ubp43 −/− cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our data showed that a variety of CXC (CXCL10, CXCL11) and CC chemokines (CCL2, 3, 4 and 5) as well as CC chemokine receptor (CCRL2) are induced by IFN-β in Ubp43 −/− BMMs (Fig. 4 and supplemental data Although there are arguments about the effect of Ubp43 deficiency on the IFN signaling pathway and the expression of IFN stimulated genes [14], our present study using Microarray analysis reveals that Ubp43 deficiency in BMMs generally enhanced the expression of genes that are induced by IFN in wild-type cells. The IFN hypersensitivity of Ubp43 −/− cells and subsequent higher induction of immune response related genes in Ubp43 −/− cells (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…However, the expression of three other IFN-induced genes, GBP1, IRF1, and Mx1, remained unaffected [14]. All five genes were in our list as ISGs in Ubp43 −/− BMM.…”
Section: Confirmation Of Gene Inductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recent studies have identified Ͼ100 target proteins of ISG15, which encompass diverse cellular pathways (15)(16)(17). However, the consequence of ISGylation of target proteins and thus the cellular function(s) of ISG15 remain unknown (18,19).…”
mentioning
confidence: 99%
“…Furthermore, ISG15 can inhibit the budding of certain viruses and modify viral proteins, and some viruses have developed strategies to inhibit ISGylation, underscoring the function of ISG15 and ISGylation in the antiviral response [6]. However, other viruses-such as vesicular stomatitis and lymphocytic choriomeningitis virus-have similar effects on ISG15 -/-and wild-type mice [7], suggesting specialized functions of ISGylation after viral infection. In addition, upfront hot of f the press a closer look at the role of ISG15 in regulating human viruses complicates the picture further: ISG15 has been found to stimulate rather than inhibit hepatitis C virus production in vitro, probably by preventing the degradation of viral proteins through competition between ISGylation and ubiquitylation [8].…”
Section: Hot Off the Pressmentioning
confidence: 99%